2008
DOI: 10.1007/s11270-008-9957-8
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Association in Plants Growing on Metal-Contaminated and Noncontaminated Soils Adjoining Kanpur Tanneries, Uttar Pradesh, India

Abstract: Commonly occurring plant species on metal-contaminated soils and noncontaminated soils adjoining Kanpur Tanneries, Uttar Pradesh, India were surveyed for arbuscular mycorrhizal association. In the present study, pH, electric conductivity (E.C.), organic carbon, macronutrients (available phosphorus, available potassium), micronutrients (Cu and Zn), and toxic metals (Cr, Cd, Pb) were higher in metal-contaminated site compared to noncontaminated site. These factors were also significantly different between metal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 40 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…AMF inoculation has become a prospective tool for enhancing plant tolerance to environmental stress conditions in metal-contaminated soils. Many examples from the literature illustrate this role of arbuscular mycorrhiza symbiosis, but progress towards understanding the cellular mechanisms utilized by AMF to metabolize heavy metals and alleviate their cytotoxicity has been made only recently (Lanfranco 2002), and the underlying mechanisms are not yet fully understood (Khade and Alok 2009). For example, the occurrence of AMF in Nihyperaccumulating plant species naturally found on metalrich soils offers possibilities of using heavy metal-hyperaccumulating plants together with AMF for phytoremediation strategies (Göhre and Paszkowski 2006).…”
Section: Am Symbiosis Increase Grapevine Tolerance To Heavy Metalsmentioning
confidence: 99%
“…AMF inoculation has become a prospective tool for enhancing plant tolerance to environmental stress conditions in metal-contaminated soils. Many examples from the literature illustrate this role of arbuscular mycorrhiza symbiosis, but progress towards understanding the cellular mechanisms utilized by AMF to metabolize heavy metals and alleviate their cytotoxicity has been made only recently (Lanfranco 2002), and the underlying mechanisms are not yet fully understood (Khade and Alok 2009). For example, the occurrence of AMF in Nihyperaccumulating plant species naturally found on metalrich soils offers possibilities of using heavy metal-hyperaccumulating plants together with AMF for phytoremediation strategies (Göhre and Paszkowski 2006).…”
Section: Am Symbiosis Increase Grapevine Tolerance To Heavy Metalsmentioning
confidence: 99%
“…The importance of AM fungi relies on their capacity to increase water and nutrient uptake, mainly uptake of P, in low-fertility soils (Schneider et al, 2013). A number of AM fungi like Glomus, Gigaspora, and Entrophospora inhabit metal-contaminated soils, among which Glomus species are the most common (Khade and Adholeya, 2009), indicating their HM tolerance (Vallino et al, 2006;Kapoor and Bhatnagar, 2007;Upadhyaya et al, 2010;Bona et al, 2011). Because of the dominance of Funneliformis mosseae in metal-polluted soils, its association with crop plants can be highly useful in conferring metal tolerance (Repetto et al, 2007;Andrade et al, 2008;Garg and Chandel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that AM fungi can colonize plant roots in metal contaminated soil [11][12][13][14][15][16][17][18][19][20][21][22][23] and it has been commonly observed that AM fungi increases shoot uptake of metals [24][25] in severely contaminated soils. In addition, AM fungi could protect plants against harmful effects of metals [26] and respond to water deficit at morphological, anatomical and cellular levels with modifications.…”
Section: Introductionmentioning
confidence: 99%